OBTAINING ADDITIONAL ELECTRICAL ENERGY IN THE AIRCRAFT TURBOJET ENGINE DUE TO THE SEEBECK EFFECT - Татарчук, Тетяна; Засовенко, Андрій; Чиж, Дар’я; Сапронов, Іван (SWorldJournal, 2024)
In today's world, most airplanes take to the skies thanks to modernized and highly efficient engines. Almost all aircraft use dual-circuit turbojet engines, which divide the air flow at the entrance into two streams: cold and hot. Due to this, the interna